Rancang Bangun Sistem Peringatan Dini Bencana Hidrometeorologi Berbasis Internet of Thing (IoT) Di BMKG - Nakiatun Niswah; Suroso Suroso; Sopian Soim (SMATIKA JURNAL : STIKI Informatika Jurnal, 2021)
A hydrometeorological disaster is a disaster that is influenced or its impact is triggered by weather and climate conditions with various parameters. For example, increased rainfall, extreme temperatures, extreme weather such as heavy rain accompanied by strong winds and lightning or lightning, and so on. Hydrometeorological Disaster Early Warning System is a system that serves to provide early warnings for hydrometeorological disasters in the form of pop ups that will be sent via Gmail and also view maps of hydrometeorological disaster prone points and provide information on roads in Palembang that are affected by hydrometeorological disasters. There are also several additional features that have been integrated from the official website Radar.cuacasumsel.com owned by BMKG Palembang. These features include hot spots, 00 UTC Wind analysis, 12 UTC analysis, Rain potential satellite, and Himawari satellite. Where the system can be displayed via a mobile phone or computer that is connected to the internet network through a website in real time based on the Internet of Things. The website will use MYSQL, PHP, CSS, JavaScript, JASON and GIS languages. Keywords: Internet of Thing (IoT), Early Warning System, Gmail, Website, Maps.